2020
DOI: 10.1159/000506405
|View full text |Cite
|
Sign up to set email alerts
|

Increased Release of Proinflammatory Proteins in Primary Human Adipocytes and Activation of the Inflammatory NFĸB, p38, and ERK Pathways upon Omentin Treatment

Abstract: Objectives: To investigate the impact of omentin on the release of inflammation-related biomarkers and inflammatory pathways in primary human adipocytes. Methods: Adipocytes were treated with or without omentin (500 and 2,000 ng/mL), and the supernatants were analyzed for inflammation-related biomarkers using proximity extension assay technology. Potential upstream regulators of the omentin-stimulated proteins were identified using Ingenuity Pathway Analysis. Protein levels of components of inflammatory pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…ERK1/2 signaling pathway is one of CRABP1 targets [ 42 ]. ERK1/2 regulates numerous cellular processes in adipocytes, and its activity has to be controlled to maintain adipocyte health and function [ 17 19 ]. This current study first detected defect in adiponectin production in CKO adipocytes associated with the obese and inflammatory phenotype of CKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK1/2 signaling pathway is one of CRABP1 targets [ 42 ]. ERK1/2 regulates numerous cellular processes in adipocytes, and its activity has to be controlled to maintain adipocyte health and function [ 17 19 ]. This current study first detected defect in adiponectin production in CKO adipocytes associated with the obese and inflammatory phenotype of CKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple human studies have demonstrated mitochondrial defects in adipocytes of people with obesity [ 13 16 ]. Numerous studies have attempted to understand the molecular mechanisms underlying adipocyte dysfunction; one mechanism involves the ERK1/2 signaling pathway which contributes to adipose tissue inflammatory response [ 17 ], promotes adipocyte differentiation and hypertrophy [ 18 , 19 ] and is also associated with mitochondria-mediated death [ 20 ]. Therefore, it is generally believed that a well-controlled ERK1/2 signaling pathway in adipocytes is important for the maintenance of healthy adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both adiponectin and omentin seem to exert both anti-inflammatory and pro-inflammatory effects according to the cell-specific differences in the adiponectin-and omentin-induced secretory process. Indeed, on the one hand, both adiponectin and omentin induce macrophage differentiation towards the M2 phenotype [31] and inhibit the secretion of inflammatory cytokines, such as TNFα and IL-6 [34][35][36][37]. On the other hand, adiponectin and omentin promote the secretion of pro-inflammatory cytokines (e.g., IL-6 [38,39], IL-1, IFNγ [40]) and chemokines (e.g., MIP1α [39]) from activated CD4 + T cells [40] and stimulate the activation of inflammatory pathways, such as NF-kB signaling, or the shift towards the M1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that adipocytokines are involved in the inflammatory response, which directly promotes the occurrence of CAD. Adipose tissue secretes many adipokines including adiponectin, chemerin, omentin-1, leptin, resistin, retinol binding protein 4, tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) (3,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…There was significant correlation between the plasma level of hsCRP and angiographic severity of coronary atherosclerosis as assessed by Gensini score. In patients with ACS elevated hsCRP is associated with higher rate of complication (12,22) .…”
Section: Discussionmentioning
confidence: 99%